Diversity as an opportunity or a challenge? A cross-national study of ethnic diversity and students' generalized trust. (January 2021) - Choi, Soobin; Lee, Moosung
Highlights: We explore how ethnic diversity at the macro-level relates to students' generalized trust by using cross-national data. Our analysis shows a positive relationship between ethnic diversity and students' generalized trust. This relationship is inverted U-shaped curvilinear rather than linear, indicating that the positive relationship levels off and turns negative. Students' educational experiences such as relations at school are also significantly associated with generalized trust. Ethnic diversity at the macro-level is still the most powerful factor in our analysis predicting students' generalized trust. Abstract: In this study, we explore how ethnic diversity at the macro-level relates to students' generalized trust by using cross-national data. Our analysis shows a positive relationship between ethnic diversity and generalized trust. This relationship is, however, inverted U-shaped curvilinear rather than linear, indicating that the positive relationship levels off and turns negative. While we also find that students' educational experiences such as social relations at school are positively associated with generalized trust, ethnic diversity at the macro-level is still the most powerful factor in our analysis predicting students' generalized trust. Theoretical and practical implications are discussed.